2013
DOI: 10.7224/1537-2073.2012-036
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Disease-Modifying Therapy and Depression in Multiple Sclerosis

Abstract: Many prescribers of disease-modifying therapies (DMTs) for multiple sclerosis (MS) believe that interferon beta (IFNβ) is more likely than glatiramer acetate (GA) to increase depression during the course of MS treatment. Therefore, newly diagnosed patients with a history of depression are often placed on GA therapy from the onset of MS treatment. The aim of this study was to examine the relationship between DMT type and depression among patients with relapsing-remitting MS (RRMS). Patients with RRMS who were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…Moroeover, many recent studies showed that increased incidence of depression in MS patients is associated with IFNβ therapy [46, 47]. Contrary, Kirzinger et al [48] indicated no differences in mean BDI score in MS patients after over 48 months of disease-modifying therapy. In our study we did not observe any differences in mean BDI scores between pre-treated patients and patients treated with interferons or glatiramer acetate, but there were differences observed between pre-treated and mitoxantrone treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moroeover, many recent studies showed that increased incidence of depression in MS patients is associated with IFNβ therapy [46, 47]. Contrary, Kirzinger et al [48] indicated no differences in mean BDI score in MS patients after over 48 months of disease-modifying therapy. In our study we did not observe any differences in mean BDI scores between pre-treated patients and patients treated with interferons or glatiramer acetate, but there were differences observed between pre-treated and mitoxantrone treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with a study showing that interferon or glatiramer acetate treatment has no effect on depression as measured by the BDI. 31 Furthermore, subcutaneous interferon beta-1a was not found to have …”
Section: Mood and Cognitionmentioning
confidence: 98%
“…Unfortunately, there is some evidence that IFNB treatment exacerbates depressive symptoms more likely than GA (Pandya and Patten, 2002 ; Goëb et al, 2003 ; Arnett and Randolph, 2006 ), therefore in patients with a history of depression GA treatment is often preferred (Wilken and Sullivan, 2007 ). However, this issue seems not entirely solved, with some studies reporting no differences between IFNB and GA (Kirzinger et al, 2013 ) or no significant beneficial effect of GA on mood-related outcomes (Jongen et al, 2010 ).…”
Section: The Impact Of Ms Drugs On Behavioral Outcomes: the Example Omentioning
confidence: 99%